Preoperative Nutrition Support May Reduce the Prevalence of Postoperative Pancreatic Fistula after Open Pancreaticoduodenectomy in Patients with High Nutritional Risk Determined by NRS2002. (21st May 2021) - Xu, Jing-Yong; Tian, Xiao-Dong; Song, Jing-Hai; Chen, Jian; Yang, Yin-Mo; Wei, Jun-Min
Abstract : Background . Clinically relevant postoperative pancreatic fistula (CR-POPF) is a severe complication which may be caused by a perioperative nutrition problem. We aimed to study whether patients with high nutritional risk (NRS 2002 score ≥ 5 ) might benefit from preoperative nutrition support regarding the risk of CR-POPF after open pancreaticoduodenectomy. Methods . Consecutive patients undergoing open pancreaticoduodenectomy with complete record of NRS2002 at two Chinese institutions between 2013 and 2018 were analysed. CR-POPF was diagnosed following the 2016 ISGPS criteria. Nutrition support included oral nutrition supplement and enteral and parenteral nutrition. Clinical and economic outcomes were analysed. Results . 522 cases were included. 135 cases (25.9%) were at high nutritional risk (NRS 2002 score ≥ 5 ), among which 41 cases (30.4%) received preoperative nutrition support. The CR-POPF rate was significantly lower in the preoperative nutrition support group compared with the no nutrition support group (12.2% versus 28.7%, P = 0.038 ). Multivariate analysis showed that preoperative nutrition support was a protective factor for CR-POPF in patients at high risk [OR 0.339, 95% CI (0.115-0.965), P = 0.039 ]. Higher albumin and a larger diameter of the main pancreatic duct were found to be other protectors for CR-POPF. Conclusions . Patients with high nutritional risk (NRS 2002 score ≥ 5 ) may profit from preoperative nutritional support manifested in the reduction of CR-POPF.